Literature Review: Peringkat PROPER sebagai Cerminan Implementasi Akuntansi Keberlanjutan dan Dampaknya bagi Perusahaan serta Masyarakat - Hidayat, Nurul Aulia; Azizah, Nabila Nurul; Mangeka, Andreas Caesario; Said, Darwis; Nagu, Nadirah (JURNAL MANAJEMEN PENDIDIKAN, 2026)
LITERATURE REVIEW: PROPER RANKING AS A REFLECTION OF THE IMPLEMENTATION OF SUSTAINABILITY ACCOUNTING AND ITS IMPACT ON COMPANIES AND SOCIETYThis study aims to examine the relationship between the Corporate Performance Rating Assessment Program in Environmental Management (PROPER) and the implementation of sustainability accounting, as well as its impacts on companies and society. Through a literature review approach covering ten relevant articles published between 2015 and 2025, this study synthesizes findings regarding the role of PROPER as both an instrument for evaluating environmental performance and a signal of corporate sustainability. The results indicate that PROPER encourages companies to enhance the transparency of environmental reporting, allocate costs related to waste management and conservation, and optimize resource utilization to reduce ecological impacts. Most studies find that attaining a high PROPER rating positively contributes to firm value, reputation, social legitimacy, and stakeholder relationships. However, several studies reveal that PROPER’s impact is not always consistent; high ratings sometimes do not reflect substantive operational improvements, particularly when companies focus more on fulfilling administrative requirements. In addition, certain environmental disclosures may reduce firm value when the information highlights unresolved risks and negative impacts. From a societal perspective, PROPER has the potential to improve environmental quality and well-being through pollution reduction and strengthened public oversight. Nevertheless, these benefits are not always maximized when companies pursue only formal compliance without long-term sustainability commitment. Overall, this review provides a conceptual foundation for future research on the factors influencing the effectiveness of PROPER in promoting more comprehensive and impactful corporate sustainability practices.